A Map of Understanding The Riskiness of Trust in the World of the Early Christians - Alexander, Loveday (2018)
Faith is an important concept in early Christianity. But what did the word pistis (and its Latin equivalent fides) mean in the everyday language of Greeks and Romans? In her important study, Teresa Morgan rightly insists that we need to pay as much attention to the way words worked in the mentalité of the wider social world with which Christians were seeking to communicate as we do to the ways they are used in the New Testament. This article seeks to summarize Morgan's understanding of pistis in the classical world and its impact on NT texts, focusing on the two major themes of pistis as relationship (believing/trusting in) and pistis as propositional belief (believing that).
Keywords: BELIEF & doubt; Bible. New Testament; Church History -- Primitive & early church, ca. 30-600; Communication; Faith; Romans; mentalité; pistis/fides; Relationship; risky; Trust; trustworthy; Rezension